PENERAPAN STRATEGI PENEMUAN TERBIMBING UNTUK MENINGKATAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK AMAL IKHLAS RUMBAI PEKANBARU - Eliwarti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the low cognitive abilities of children at TK Amal Ikhlas Pekanbaru. This condition is indicated by: (1) children’s low ability in cognitive learning; (2) children’s difficulty in expressing what they have learned through trial activities; and (3) children’s limited memory in cognitive learning. Therefore, it is necessary to apply a concrete learning approach suitable for the children’s cognitive abilities, namely the guided discovery strategy. The research problem is formulated as follows: Can the use of the guided discovery strategy improve the cognitive abilities of children aged 5–6 years at TK Amal Ikhlas Pekanbaru? The aim of this study is to determine whether the implementation of the guided discovery strategy can enhance the cognitive abilities of children aged 5–6 years at TK Amal Ikhlas Pekanbaru. The method used in this research is classroom action research (CAR), involving 20 children as research subjects, consisting of 12 boys and 8 girls. Data collection techniques include observation and documentation, while data analysis is conducted using percentage techniques. The results of the study indicate that children’s cognitive abilities improved over the course of the research. Initial data showed an average cognitive ability score of 31.3. In the first cycle, the first meeting yielded 39.3, and the second meeting reached 48.5. In the second cycle, the first meeting showed 56.3, and the second meeting reached 67.8. Based on these results, it can be concluded that the application of the guided discovery strategy effectively improves the cognitive abilities of children aged 5–6 years at TK Amal Ikhlas Pekanbaru. The percentage increase in cognitive abilities can be observed from the pre-cycle stage (before the implementation of the guided discovery strategy) to the second cycle.